2022
DOI: 10.2147/ijn.s354003
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Renewal of Extracellular Vesicles: Harmful Effects on Embryo Development in vitro

Abstract: Background Extracellular vesicles (EVs), as a promising platform for drug delivery, have attracted much attention. Degradation and regeneration of EVs maintain their homeostasis in vivo, but this regeneration is missing in the in vitro culture (IVC) system, which is likely to lead to negative effects. It is particularly concerning that most studies involving the addition of EVs in IVC seem to overlook this point. Methods We used rabbit embryos and oviduct fluid EVs as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The pig is the best cloned animal species, but the low implantation ability of cloned embryos has been a major obstacle to its development [31]. There are many differences in the extracellular environment between embryos grown in vitro and those grown in vivo [32]. On one hand, in the early stage of embryo development, cloned embryos grown in vitro have stable MAPK level loss compared to IVF embryos [33,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pig is the best cloned animal species, but the low implantation ability of cloned embryos has been a major obstacle to its development [31]. There are many differences in the extracellular environment between embryos grown in vitro and those grown in vivo [32]. On one hand, in the early stage of embryo development, cloned embryos grown in vitro have stable MAPK level loss compared to IVF embryos [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Relevant data have shown that OEC EVs can greatly improve the success rate of embryo IVF and reduce the rate of multiple sperm entry [39]. Other relevant data indicate that the loss of OEC EVs has a significant impact on embryo development [32]. OEC EVs can reduce the damage caused by reactive oxygen species.…”
Section: Discussionmentioning
confidence: 99%
“…Superoxide dismutase 2 (SOD2) and glutathione peroxidase 3 (GPX3) are present in exosomes, and both proteins are involved in antioxidant defense [ 93 , 94 ]. During pro-inflammatory conditions, proteins such as SOD2 and GPX3 are upregulated.…”
Section: Role Of Exosomes In Allergic Diseasesmentioning
confidence: 99%